Comorbid chronic diseases, discordant impact on mortality in older people: a 14-year longitudinal population study. Issue 12 (23rd October 2009) - Caughey, G E; Ramsay, E N; Vitry, A I; Gilbert, A L; Luszcz, M A; Ryan, P; Roughead, E E
Abstract : Objectives: To determine the impact of comorbid chronic diseases on mortality in older people. Design: Prospective cohort study (1992–2006). Associations between numbers of chronic diseases or mutually exclusive comorbid chronic diseases on mortality over 14 years, by Cox proportional hazards model adjusting for sociodemographic variables or Kaplan–Meier analyses, respectively. Setting: Population based, Australia. Participants: 2087 randomly selected participants aged ≥65 years old, living in the community or institutions. Main results: Participants with 3–4 or ≥5 diseases had a 25% (95% CI 1.05 to 1.5, p=0.01) and 80% (95% CI 1.5 to 2.2, p<0.0001) increased risk of mortality, respectively, by comparison with no chronic disease, after adjusting for age, sex and residential status. When cardiovascular disease (CVD), mental health problem or diabetes were comorbid with arthritis, there was a trend towards increased survival (range 8.2–9.5 years) by comparison with CVD, mental health problem or diabetes alone (survival 5.8–6.9 years). This increase in survival with arthritis as a comorbidity was negated when CVD and mental health problems or CVD and diabetes were present in disease combinations together. Conclusion: Older people with ≥3 chronic diseases have increased risk of mortality, but discordant effects on survival depend on specific disease combinations. These results raise the hypothesis that patients who have an increased likelihood of opportunity for care from their physician are more likely to have comorbid diseases detected and managed.